PENGARUH JUMLAH BILAH PENGARAH ANGIN JENIS OMNIDIRECTIONAL TERHADAP KINERJA MODEL TURBIN ANGIN SAVONIUS - Indra Herlamba Siregar; Moch Effendy; Akhmad Hafidz Ainur Rasyid (Otopro, 2023)
Recently, many countries are looking for alternative energy sources that are renewable and environmentally friendly, one of which is wind energy, with Indonesia's wind energy potential of 9 GW and relatively low wind speeds and geographical position, it is necessary to develop wind turbine technology that is suitable for wind characters in Indonesia. In this research, an omnidirectional wind director model (ODGV) is developed around the savonius wind turbine which aims to improve the performance of the savonius wind turbine model. The ODGV consists of several blades that function to direct the wind at 45o  counterclockwise, with the aim of accelerating the flow so as to increase the positive torque of the concave side blades and reduce the negative torque of the convex side blades of the savonius wind turbine model. An open-type wind tunnel was used to test the savonius wind turbine model with ODGVs. Five ODGVs were developed in this study, using 4, 6, 8, 12, and 16 directional blades with a width of 5cm. The data were analyzed using descriptive analysis. The results show that the ODGV can substantially improve the rotor performance, depending on the number of directional blades. The ODGV with 12 directional blades produced the greatest effect on the performance of the savonius wind turbine model at Re = 93269 which could increase the Cp 69.15% more than the savonius wind turbine model without ODGV. As the Reynolds number increases, the ODGV tends to significantly improve the performance of the savonius wind turbine model.